Adipose tissue as mesenchymal stem cells source in equine tendinitis treatment - De Mattos Carvalho, Armando; Hussni, Carlos Alberto [UNESP]; Alves, Ana Liz Garcia [UNESP] (Universidade Estadual de Londrina, 2016)
Tendinitis is an important high-relapse-rate disease, which compromises equine performance and may result in early athletic life end to affected animals. Many therapies have been set to treat equine tendinitis; however, just few result in improved relapse rates, quality of extracellular matrix (ECM) and increased biomechanical resistance of the treated tissue. Due to advances in the regenerative medicine, promising results were initially obtained through the implantation of mesenchymal stem cells (MSC) derived from the bone marrow in the equine tendon injury. Since then, many studies have been using MSCs from different sources for therapeutic means in equine. The adipose tissue has appeared as feasible MSC source. There are promising results involving equine tendinitis therapy using mesenchymal stem cells from adipose tissue (AdMSCs).
Keywords: Regenerative medicine; Stem cells; Tendon; Therapy